2020
DOI: 10.3390/atmos11060656
|View full text |Cite
|
Sign up to set email alerts
|

Elevation Effects on Air Temperature in a Topographically Complex Mountain Valley in the Spanish Pyrenees

Abstract: Air temperature changes as a function of elevation were analyzed in a valley of the Spanish Pyrenees. We analyzed insolation, topography and meteorological conditions in order to understand how complex topoclimatic environments develop. Clustering techniques were used to define vertical patterns of air temperature covering more than 1000 m of vertical elevation change. Ten locations from the bottom of the valley to the summits were monitored from September 2016 to June 2019. The results show that (i) night-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Additionally, areas characterized by minimal variations in elevation were included in the assessment, given the substantial impact of elevation on temperature patterns. Under the premise that elevated altitudes are associated with lower temperatures, as documented in prior investigations [72,73], a temperature gradient of approximately 6.5 • C per one thousand meters alteration in elevation is observed [73,74].…”
Section: Selection Of Agricultural Areas Influenced By Meteorological...mentioning
confidence: 87%
“…Additionally, areas characterized by minimal variations in elevation were included in the assessment, given the substantial impact of elevation on temperature patterns. Under the premise that elevated altitudes are associated with lower temperatures, as documented in prior investigations [72,73], a temperature gradient of approximately 6.5 • C per one thousand meters alteration in elevation is observed [73,74].…”
Section: Selection Of Agricultural Areas Influenced By Meteorological...mentioning
confidence: 87%
“…Temperature is most often the dominant abiotic factor affecting herbivorous insects (Reymond et al, 2013). Temperature fluctuation is also wider at higher elevations in the Pyrenees (Navarro‐Serrano et al, 2020). Although Steven's extension to Rapaport's rule (i.e., the elevational range of a species is wider at higher elevations) is controversial (Kim et al, 2019; McCain & Bracy Knight, 2013), Rasmann et al (2014) found evidence for less host specialization of Buprestidae species (a saproxylic Coleoptera family) and Apiformes (a bee group) at higher elevations in the Swiss Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Although the spatial resolution is high (0.1°) and the temperature was adjusted to the elevation of the sites with a temperature lapse rate, the temperature data still might be different from the actual temperature at the forest canopy. For example, some meteorological phenomena, such as air temperature inversion or the effect of topography on local air circulation and land-atmosphere feedbacks, can hardly be accounted for by a simple lapse rate 51,52 . Third, although the Unified model integrates most of the up-to-date known causal relationships between temperature and bud development 19 , it may still miss some unknown mechanisms affecting bud phenology.…”
Section: Explaining the Declining Sensitivity Of Lud To Warmingmentioning
confidence: 99%